Simulations as Scaffolds in Science Education - Renken, Maggie; Peffer, Melanie; Otrel-Cass, Kathrin; Girault, Isabelle; Chiocarriello, Augusto (SpringerBriefs in Educational Communications and Technology,, 2016)
This book outlines key issues for addressing the grand challenges posed to educators, developers, and researchers interested in the intersection of simulations and science education. To achieve this, the authors explore the use of computer simulations as instructional scaffolds that provide strategies and support when students are faced with the need to acquire new skills or knowledge. The monograph aims to provide insight into what research has reported on navigating the complex process of inquiry- and problem-based science education and whether computer simulations as instructional scaffolds support specific aims of such pedagogical approaches for students.